Manajemen Risiko pada Pembiayaan Murabahah Guna Meningkatkatkan Kinerja Keuangan: Studi Kasus Di Baitul Maal Wat Tanwil (BMT) Maslahah Cabang Kotaanyar Probolinggo - Cici Widya Prasetyandari; Rasyidi Rasyidi (Dharma Ekonomi, 2025)
Risk is an uncertainty that causes losses to the company. So this uncertainty must be managed properly. This study aims to determine the implementation of murabahah financing risk management at BMT Maslahah Kotaanyar Probolinggo. The research method used is qualitative research. Data sources were obtained through interviews, observations and documentation. Based on the results of the analysis, it is known that BMT Maslahah is still experiencing problems with murabahah financing, there are several customers who delay in fulfilling their obligations. Therefore, it is necessary to implement murabahah financing risk management in order to minimize the problems that will occur. BMT Maslahah Kotaanyar Branch has so far been quite effective in implementing murabahah financing risk management. However, BMT Maslahah Kotaanyar Branch must continue to apply the 5C principle in providing credit, in order to avoid the risk of problematic financing in the future.